Analysis Forecasting Sales With Single Exponential Smoothing Method - Abraham Manalu; Dewi Roito; Eika Rizkiadina; Yonata Laia (LPPM Universitas Bina Sarana Informatika, 2022)
Currently, as we know that the use of computer-based systems, almost everyone's activities depend on computer-based systems. one that is currently very adequate in the use of the application is the sales system, in this research the problem faced by the company is the difficulty of determining the amount of inventory stock each month. The reason is because the number of types of goods is not small so this is the cause of the lack of fulfillment of consumer demand every day. Companies that do have a number of inventories whose stock or inventory is on a large scale, so it needs a special system in this control so that the required inventory is always met, the point is for the company's income to increase even more. Researchers as technology-savvy people provide ideas for companies to use a system that can minimize the lack of goods inventory. This is what the researcher wants to solve the problem with the single exponential smoothing method. Because the method used can do fortune-telling in the short term for example 1 month ahead. The results of this study succeeded in predicting the amount of inventory in stock every month.